The α-thalassemias. - Piel, F; Weatherall, D (Massachussetts Medical Society, 2014)
More than 100 varieties of α-thalassemia have been identified. Their geographic distribution and the challenges associated with screening, diagnosis, and management suggest that α-thalassemias should have a higher priority on global public health agendas.